SINTESIS DAN KARAKTERISASI KATALIS BERBASIS Ni-MCM-41 SEBAGAI PERENGKAH UNTUK MINYAK SAWIT - , Lailatul Badriyah ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Synthesis of mesoporous MCM-41 and NiMCM-41 materials by sol-gel method under Si/Ni ratio of 50 had ben conducted oil. The last material was then modified as Ni/NiMCM-41 and Co/NiMCM-41 by impregnation methode. These materials were applied as catalyst in the cracking process of palm to produced the highly product of gasoline. The synthesis was carried out using sodium silicate solution 25% as silica precursors, NiCl2Î6H2O as nickel precursors, and Co(NO3)2Î6H2O as kobal precursors. These materials were characterized by X-Ray Diffraction (XRD), Fourier Transformation Infra Red Spectroscopy (FTIR), Silicon Nuclear Magnetic Resonance (29Si-NMR), Atomic Adsorption Spectroscopy (AAS), and Gas Sorption Analysis (GSA), Transmission Electron Microscope (TEM). The products of the cracking were analyzed by Gas Chromatography-Mass Spectroscopy (GC-MS). The TEM analysis results shown that there was Ni in the framework with the hexagonal porous shape, the pore size of MCM-41<NiMCM-41, the acidity of MCM-41< Ni/NiMCM-41< NiMCM-41< Co/NiMCM-41. NiMCM-41 more stabilizer than catalyst of MCM-41 shown that on itâcristalinity. The conversion of product (wt%) was Co/NiMCM-41 (89,53 wt%) > NiMCM-41 (83,76 wt%) > Ni/NiMCM-41 (75,59 wt%) > MCM-41 (58,85 wt%) respectively. The products of biogasoline (%) was Co/NiMCM-41 (100 wt%) > NiMCM-41 (99,13 wt%) > Ni/NiMCM-41 (98,13 wt%) >MCM-41 77,57 wt%) respectively.